Alternative transcription start site selection in Mr-OPY2 controls lifestyle transitions in the fungus Metarhizium robertsii. Issue 1 (December 2017) - Guo, Na; Qian, Ying; Zhang, Qiangqiang; Chen, Xiaoxuan; Zeng, Guohong; Zhang, Xing; Mi, Wubing; Xu, Chuan; St. Leger, Raymond; Fang, Weiguo
Abstract Metarhizium robertsii is a versatile fungus with saprophytic, plant symbiotic and insect pathogenic lifestyle options. Here we show thatM. robertsii mediates the saprophyte-to-insect pathogen transition through modulation of the expression of a membrane protein, Mr-OPY2. Abundant Mr-OPY2 protein initiates appressorium formation, a prerequisite for infection, whereas reduced production of Mr-OPY2 elicits saprophytic growth and conidiation. The precise regulation of Mr-OPY2 protein production is achieved via alternative transcription start sites. During saprophytic growth, a single long transcript is produced with small upstream open reading frames in its 5′ untranslated region. Increased production of Mr-OPY2 protein on host cuticle is achieved by expression of a transcript variant lacking a small upstream open reading frame that would otherwise inhibit translation of Mr-OPY2. RNA-seq and qRT-PCR analyses show that Mr-OPY2 is a negative regulator of a transcription factor that we demonstrate is necessary for appressorial formation. These findings provide insights into the mechanisms regulating fungal lifestyle transitions. The fungusMetarhizium robertsii can act as a saprophyte, plant symbiont and insect pathogen. Here, the authors show that the use of alternative transcription start sites controls the expression of membrane protein Mr-OPY2, which in turn modulates the saprophyte-to-pathogen transition.